Miłosz wobec Brzozowskiego. O "Człowieku wśród skorpionów..." i nie tylko - Panek, Sylwia (My University, 2012)
The aim of the author of the article is to investigate Miłosz’s relation to Stanisław Brzozowski. Proceeding from the interpretation of Miłosz’s Człowiek wśród skorpionów..., and diagnosing his personal motivation for turning to Brzozowski’s works in 1963, the author investigates the avenues of dialogue between Miłosz and Brzozowski, and their unsystematically expresses common points. The article, thus, presents various stages of influence of Brzozowski’s work and ideas on Miłosz: from the 1930s, when Miłosz was inspired by Brzozowski’s left-wing fanaticism, through the common opposition against anti-intellectualism and the Polish identity understood as a set of Romantic symbols and gestures, up to the fascination with Russian culture and Marxism. The deepest affinity of both authors seems to be the attitude of anthropocentrism, identified and exposed by Miłosz himself, and understood as hostility towards nature and belief in nature’s determinism, but also as a formula that gives coherence to the philosophical themes, found in both authors’ work, which are thought to be polarised and incompatible. In the conclusion, the author of the article states that positioning himself with reference to Brzozowski was, for Miłosz, a tool of self-creation, an attempt to control the reception and interpretation of his own work, and to place Miłosz in a separate and exceptional position, akin to the position of Brzozowski, the extraordinary and unrecognized philosopher and critic of Polish early modernism.
Miłosz’s Response to Brzozowski. On "Człowiek wśród skorpionów..." ["Man among Scorpions..."] and More
Keywords: Czesław Miłosz; Stanisław Brzozowski; Miłosz’s self-creation; Marxism; Russia in Miłosz’s works